2010
DOI: 10.3758/s13423-010-0020-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling working memory: a computational implementation of the Time-Based Resource-Sharing theory

Abstract: Working memory is a core concept in cognition, predicting about 50% of the variance in IQ and reasoning tasks. A popular test of working memory is the complex span task, in which encoding of memoranda alternates with processing of distractors. A recent model of complex span performance, the Time-Based-Resource-Sharing (TBRS) model of Barrouillet and colleagues, has seemingly accounted for several crucial findings, in particular the intricate trade-off between deterioration and restoration of memory in the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
237
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(246 citation statements)
references
References 74 publications
7
237
0
2
Order By: Relevance
“…It is worth noting that the current pattern is reasonably in line with common estimations of encoding speed (500 ms per item; e.g., Jolicoeur & Dell'Aqua, 1998;Oberauer & Lewandowsky, 2011), with clear evidence for spontaneous refreshing when items are presented at a rate that allows for refreshing after the just-presented memory item is fully Refreshing in WM 32 encoded (i.e., when items are presented at a rate of 1 per 1000 ms), and clear evidence against spontaneous refreshing when items are presented at a rate that is barely enough for encoding to be fully accomplished before the next list item is presented and that thus, does not allow for refreshing after encoding (i.e., when items are presented at a rate of 1 per 350 ms). In contrast, the current pattern is not in line with slower estimations of encoding speed (1000 ms and more per item; e.g., Bayliss et al, 2015) because our results indicate that the last-presented item is no longer in the focus of attention 1000 ms after its onset (i.e., No delay conditions of Experiments 1, 3 and 5).…”
Section: The Last-presented Benefit As An Independent Direct Index Osupporting
confidence: 56%
“…It is worth noting that the current pattern is reasonably in line with common estimations of encoding speed (500 ms per item; e.g., Jolicoeur & Dell'Aqua, 1998;Oberauer & Lewandowsky, 2011), with clear evidence for spontaneous refreshing when items are presented at a rate that allows for refreshing after the just-presented memory item is fully Refreshing in WM 32 encoded (i.e., when items are presented at a rate of 1 per 1000 ms), and clear evidence against spontaneous refreshing when items are presented at a rate that is barely enough for encoding to be fully accomplished before the next list item is presented and that thus, does not allow for refreshing after encoding (i.e., when items are presented at a rate of 1 per 350 ms). In contrast, the current pattern is not in line with slower estimations of encoding speed (1000 ms and more per item; e.g., Bayliss et al, 2015) because our results indicate that the last-presented item is no longer in the focus of attention 1000 ms after its onset (i.e., No delay conditions of Experiments 1, 3 and 5).…”
Section: The Last-presented Benefit As An Independent Direct Index Osupporting
confidence: 56%
“…Therefore, higher cognitive load implies a larger proportion of time during which refreshing is prevented, leaving memory traces to decay, and a lower proportion of time during which decay can be counteracted by refreshing. Computational modelling has shown that with these assumptions the approximately linear effect of cognitive load on serial recall performance can be explained (Oberauer & Lewandowsky, 2011).…”
Section: Cognitive Load (B1)mentioning
confidence: 99%
“…Borsboom (2006) sugiere que uno de los aspectos que han obstaculizado la integración de la psicometría en las prácticas de investigación psicológica radica en la ausencia de una teoría psicológica fuerte. Actualmente, dicha aseveración sigue siendo válida en el contexto general de la psicología; sin embargo, muchas áreas de la psicología experimental y en especial aquellas vinculadas con el uso de los modelos cognitivos formales ofrecen excelentes teorías respecto a procesos cognitivos como la memoria de trabajo (Brown, Neath & Chater, 2007;Farrell & Lewandowsky, 2002;Oberauer & Lewandowsky, 2011;Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012), el razonamiento (Anderson, Bothell, Byrne, Douglass, Lebiere, et al, 2004), la toma de decisiones rápidas (Ratcliff & McKoon, 2007) o riesgosas (Wallsten, Pleskac, & Lejuez, 2011), categorización perceptual (Nosofky, 1986), etc. En el contexto de los avances científicos respecto al conocimiento de varios procesos cognitivos la sección siguiente sugiere que al menos en el caso del estudio de la capacidad de memoria de trabajo y el estudio de la inteligencia fluida se encuentra un área fértil para la implementación de nuevas teorías y modelos psicométricos.…”
Section: Modelos Cognitivos Formales Y El Modelo Psicométrico Reflectunclassified